The Food, Feelings, and Family Study: comparison of the efficacy of traditional methods, social media, and broadcast email to recruit pregnant women to an observational, longitudinal nutrition study - Rebecca Smith; Crystal Alvarez; Sylvia Crixell; Michelle A. Lane (BMC, 2021)
Abstract Background It is well known that recruitment is a challenging aspect of any study involving human subjects. This challenge is exacerbated when the population sought is reticent to participate in research as is the case with pregnant women and individuals with depression. This paper compares recruitment methods used for the Food, Feelings, and Family Study, an observational, longitudinal pilot study concerning how diet and bisphenol A exposure affect maternal mood and cognitive function during and after pregnancy. Methods Pregnant women were recruited to this study over a period of 15 months using traditional methods, social media including paid and unpaid posts, and emails broadcast to the university community. Contingency analysis using the Pearson's Chi-square test was used to determine if recruitment method was associated with likelihood of participation. T-tests were used to analyze Facebook advertisement success. ANOVAs and Fisher exact tests were used to determine if recruitment method was related to continuous and categorical demographics, respectively. Results Social media resulted in the largest number of recruits, followed by traditional methods and broadcast email. Women recruited through social media were less likely to participate. In contrast, use of broadcast email resulted in a smaller pool of recruits but these recruits were more likely to be eligible for and complete the study. Most women recruited via social media were the result of unpaid posts to the study's Facebook page. Paid posts lasting at least 4 days were the most successful. Recruitment method was not associated with participant demographics. Conclusions Social media has the potential to recruit a large pool of potential subjects; however, when studies require a large time investment such as the case here, women recruited through social media are less likely to participate and complete the study than women recruited through other means. Trial registration N/A. This study does not describe a health care intervention.